In-vitro cytotoxicity effects and bioactive constituents of chloroform extract of Vernonia Glaberrima Welw. Ex o. Hoffm (Asteraceae) - Alhassan, A. M.; Uba, A.; Muhammad, C.; Bako, H.L.; Malami, I.; Ahmed, Qamar Uddin; Alkali, Y.I. (Usmanu Danfodiyo University, Sokoto P.M.B. 2346, Sokoto, Nigeria, 2022)
Vernonia glaberrima plant is used traditionally in the treatment of cancer, diabetes and malaria in North central Nigeria. This study was designed to evaluate the cytotoxic effect of chloroform extract of Vernonia glaberrima and isolate some bioactive constituents. Neutral red cytotoxicity assay was performed using breast cancer (MCF7), cervical cancer (HeLa) and Liver cancer (HepG2) cells upon exposure to predetermined concentrations of the chloroform extract. The cell viability was determined colorimetrically after 72 hours of incubation. The extract was fractionated using silica gel column chromatography and preparative TLC. Isolated compounds were characterized using FTIR and NMR spectroscopy. The extract inhibited 50% cell proliferation of MCF7, HeLa and HepG2 cells at an IC50 value of 14.02 ± 0.03, 15.78. ± 0.04, and 16.77± 0.1 µg/mL, respectively. Two compounds namely, lupeol (1) and betulinic acid (2) were isolated from the extract. The two isolated compounds have been previously reported in literature to possess anticancer activities. Hence, the findings from this study demonstrate the potential anticancer properties of chloroform extract of Vernonia glaberrima.